Pathogenicity Of Acuaria Hamulosa To Chicken - Ganeswara Rao Y (Department of Parasitology, College of Veterinary and Animal Sciences, 1980)
Controlled experiments were conducted with commonly occurring spirurid worm of chicken, Acuaria hamulosa, in two breeds of chicken, namely the White Leghorn (an egg strain) and the White Plymouth Rock (a broiler strain). The blood changes conducted revealed an initial leucocytosis from 14th day to 36th day, followed by heterophilia from 43rd day to 70th day post infection, and a mild eosinophilia throughout the experimental period. The infected White Plymouth Rock birds lost considerable amount of their body weight. In White Leghorn layers, there was great delay in sexual maturity and poor feed efficiency as indicated by reduced egg production. The percentage of establishment in the experiment was found to be not correlated to the infective dose. The pathological changes in the affected gizzards indicated an acute inflammation during the invasive phase of juveniles, followed by a chronic reaction, which by 60th day post infection was well established indicating the development of a host – parasite balances, towards the later stages of infection.